2000
DOI: 10.1002/(sici)1521-3986(200004)40:1/2<57::aid-ctpp57>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Ergodic Divertor (DED) for TEXTOR-94

Abstract: A Dynamic Ergodic Divertor (DED) is under construction for TEXTOR‐94. The ergodization will be achieved by a set of 16 in‐vessel perturbation — plus two compensation — coils located at the high field side of TEXTOR‐94. The coils follow helically the magnetic field lines for one toroidal turn of a preselected “resonant” magnetic flux surface and are individually fed outside the vessel allowing a large flexibility for possible interconnections. The DED‐system will operate at DC or several fixed frequencies up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…At the TEXTOR tokamak the dynamic ergodic divertor (DED) was designed as a flexible setup to investigate the generic features of stochastic magnetic boundaries [10]. As visualized in figure 1 it consists of a set of 16 + 2 coils implemented into the vacuum vessel and winding helically around the torus at the high field side (HFS).…”
Section: Introductionmentioning
confidence: 99%
“…At the TEXTOR tokamak the dynamic ergodic divertor (DED) was designed as a flexible setup to investigate the generic features of stochastic magnetic boundaries [10]. As visualized in figure 1 it consists of a set of 16 + 2 coils implemented into the vacuum vessel and winding helically around the torus at the high field side (HFS).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] have shown that the relative radial extensions of the laminar and the ergodic zones at the plasma edge strongly depend on the plasma parameters ͑plasma ␤ pol , the plasma current I p ), as well as on the divertor current. Particularly, it was found that the increase of the divertor current ͑or decrease of ␤ pol ) does not necessarily lead to a growth of field line diffusivity, which is proportional to the particle diffusion coefficient ͑see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…A tokamak has the advantages of a simpler geometry and a more pronounced MHD activity. Furthermore, TEXTOR is presently being equipped with a helical divertor 15 and then we hope to get pronounced structures on demand. …”
Section: Discussionmentioning
confidence: 99%